Control trial of porcine cysticercosis in Uganda using a combination of the TSOL18 vaccination and oxfendazole - Nsadha, Zachary; Rutebarika, Chris; Ayebazibwe, Chrisostom; Aloys, Bukenya; Mwanja, M.; Poole, Elizabeth J.; Chesang, Elizabeth; Colston, Angela; Donadeu, Meritxell; Lightowlers, Marshall W. (Springer, 2021)
Neurocysticercosis caused by Taenia solium when the parasite lodges in the central nervous system, is an important cause of human seizures and mortality in sub-Saharan Africa. The parasite is prevalent in many regions of Uganda. Pigs are intermediate hosts for T. solium , and we evaluated a T. solium control program in pigs, involving vaccination of pigs with the TSOL18 vaccine and treatment with oxfendazole.